Raw material composition for polyurethane rubber powder, polyurethane rubber powder and application thereof

Through the raw material combination and preparation method of polyurethane glue powder, the problem of the inability to dry and preparation of polyurethane dispersion into powder form and lack of reactive activity is solved, and the efficient compression and flexural resistance in the mortar is achieved, and it is suitable for continuous construction equipment.

CN119219891APending Publication Date: 2024-12-31HUNAN ZOOMLION NEO MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411341535.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing polyurethane dispersions cannot be dried and prepared into powder form, lack reactive activity, poor anti-caking performance, and insufficient compression and flexural resistance in mortar, so they cannot be applied to continuous construction equipment.

Method used

Provide a raw material combination for polyurethane glue powder, including a first material and a second material, the first material consisting of polyol, isocyanate, catalyst, protective colloid and water, and the second material consisting of isocyanate, polyol, polyvinyl alcohol and water , prepared by specific mixing and reaction steps, polyurethane powder with reactive activity and good dispersion is formed.

Benefits of technology

The prepared polyurethane powder is easy to disperse and has stable storage, and can be used in dry-mixed mortar, which significantly improves the compressive flexural strength of cement mortar, especially its flexural resistance, and is suitable for continuous construction equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059837020000111
    Figure BDA0005059837020000111
  • Figure BDA0005059837020000131
    Figure BDA0005059837020000131
  • Figure BDA0005059837020000141
    Figure BDA0005059837020000141
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a raw material composition for polyurethane rubber powder, the polyurethane rubber powder and application of the polyurethane rubber powder. The raw material composition for the polyurethane rubber powder contains a first material and a second material, wherein a composition I for forming the first material contains polyol A, isocyanate A, a catalyst, a protective colloid, an emulsifier and water I; and a composition II for forming the second material contains isocyanate B, isocyanate C, polyol B, polyvinyl alcohol and water II. The polyurethane rubber powder prepared by adopting the raw material composition for the polyurethane rubber powder is easy to disperse and stable to store, has reaction activity, and can remarkably improve the compressive strength and the breaking strength of cement mortar products when being applied to mortar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a raw material combination for polyurethane rubber powder, polyurethane rubber powder and application thereof. Background Art

[0002] Redispersible polymer latex powder refers to a polymer powder that can regenerate a stable polymer emulsion after being dispersed in water and has similar properties to the original polymer emulsion used for drying.

[0003] At present, the redispersible polymer latex powder used in dry mortar mainly includes the following types: vinyl acetate-ethylene (EVA) copolymer, vinyl acetate-vinyl ester copolymer, vinyl acetate-vinyl ester-propylene ester terpolymer, acrylate polymer, styrene-acrylic acid copolymer, and commonly used monomers such as vinyl acetate, methyl acrylate, methyl methacrylate, butyl acrylate, butadiene, styrene, 2-ethylhexyl acrylate, vinyl ester, etc. At present, the most widely used is EVA series.

[0004] However, the above-mentioned redispersible polymer latex powder is mainly modified in the form of a single-component filler, and finally exists in the mortar in the form of physical adsorption and adhesion (without reaction activity), and has limited reinforcing effect on the mortar.

[0005] Polyurethane is a block polymer composed of a flexible soft segment composed of polyester or polyether and a rigid hard segment connected by urethane, urea, etc. Due to the microphase separation caused by the thermodynamic incompatibility of the soft and hard segments of the polymer and good biocompatibility, it is endowed with excellent elasticity, wear resistance, impact resistance and tensile properties.

[0006] Due to technical limitations, polyurethane is currently mainly used in the field of building mortar in the form of a multi-component liquid, such as a four-component water-based polyurethane mortar floor material disclosed in CN105753379A and a three-component composition for manufacturing a baseboard primer or a primer coating disclosed in CN111032719A; its construction technology requirements are high and its operability time is short, and it cannot be used in continuous construction equipment. In addition, it is currently based on solvent-free polyurethane. During the production and use of the product, it is necessary to strictly pay attention to the water content of the raw materials, the base layer and the construction site. Excessive water content will cause the material to foam and the strength will be sharply reduced.

[0007] Therefore, there is an urgent need to provide a redispersible polyurethane powder to solve the defects of existing application technology: 1. The multi-component liquid material process is complicated and cannot be applied to continuous construction equipment; 2. The operating time is short; 3. The construction conditions are high and the water content needs to be strictly controlled.

[0008] CN104004160A discloses a method for preparing a highly thixotropic aqueous polyurethane dispersion for soft-feel coatings, characterized in that the preparation method comprises the following steps, wherein the parts of the substances in the following steps are calculated by mass: S1. adding 70-90 parts of polyether diol to a first reaction kettle, dehydrating; cooling, and then adding 10-30 parts of diisocyanate and 0.1-1 parts of a catalyst; S2. adding an excess of a monofunctional small molecule alcohol to the first reaction kettle, and continuing the reaction; heating, removing the excess small molecule alcohol, and cooling to obtain a polyurethane prepolymer A; S3. adding 30-80 parts of polyether diol to a second reaction kettle; 0 parts of polymer polyol, dehydrate; cool down, add 20-70 parts of diisocyanate and 0.1-1 parts of catalyst; S4. Add 1-6 parts of monomolecular diol containing carboxyl to the second reactor, continue to react; cool down, add neutralizer to obtain polyurethane prepolymer B; S5. Mix polyurethane prepolymer A and polyurethane prepolymer B at a mass ratio of 1:3-2:1; S6. Add 5-30 parts of emulsifier or aqueous solution formed by protective colloid to the mixed system formed by polyurethane prepolymer A and polyurethane prepolymer B, disperse, and then add polyamine to the mixed system to obtain the target product. Although this scheme can obtain polyurethane dispersion microspheres, the polyurethane microspheres in this scheme cannot be dried and prepared into powder, and have no reaction activity, and cannot be applied to the mortar field.

[0009] CN108623771A discloses a hydroxyl-terminated polyurethane prepolymer, characterized in that it is a reaction product of the following raw materials: a) one or more polymer polyols selected from polyether polyols and polyester polyols; b) one or more phosphate esters; and c) one or more polyisocyanates. This solution is that the oily polyurethane prepolymer is used in the field of polyurethane foam materials, cannot be dispersed in water, and cannot be used in the field of mortar.

[0010] CN118307742A discloses a method for preparing an aqueous polyurethane dispersion, comprising: preheating a diisocyanate, a polycarbonate polyol, a small molecule chain extender, a hydrophilic chain extender and a catalyst, mixing them, and reacting them under stirring to obtain a polyurethane melt; stirring and mixing the polyurethane melt with water and a weak solvent until emulsification is complete to obtain an emulsified material; reacting the emulsified material with a neutralizer to obtain a neutralized material; and removing the weak solvent in the neutralized material to obtain the aqueous polyurethane. dispersion; wherein the small molecule chain extender includes a C2-C6 diol, the hydrophilic chain extender includes one or more of dimethylolbutyric acid, 1,2-propylene glycol-3-sodium sulfonate, and 1,4-butanediol-2-sodium sulfonate; the molar ratio of the diisocyanate, the polycarbonate polyol, the small molecule chain extender, the hydrophilic chain extender, and the catalyst is (49.7-49.8):(21-26):(14-19):(10-13):(0.02-0.05). Although the scheme can obtain an aqueous polyurethane dispersion, the aqueous polyurethane dispersion in the scheme cannot be dried and prepared into a powder, and has no reaction activity, and cannot be applied to the mortar field. Summary of the invention

[0011] The purpose of the present invention is to solve the problems of the prior art polyurethane dispersion that it cannot be dried to prepare into powder, has no reactivity, has poor anti-caking performance, and has poor compression and flexural properties after being applied to mortar.

[0012] In order to achieve the above-mentioned object, the first aspect of the present invention provides a raw material combination for polyurethane rubber powder, wherein the combination contains a first material and a second material, and the mass ratio of the first material to the second material is 1:3-5;

[0013] The composition I forming the first material contains: polyol A, isocyanate A, catalyst, protective colloid, emulsifier, water I; the isocyanate A is selected from cycloalkyl diisocyanate and / or xylene diisocyanate; the polyol A is a dihydric or higher alcohol;

[0014] Relative to 100 parts by weight of polyol A, the content of isocyanate A is 8-16 parts by weight, the content of the catalyst is 0.2-0.4 parts by weight, the content of the protective colloid is 8-18 parts by weight, the content of the emulsifier is 0.05-0.4 parts by weight, and the content of water I is 75-95 parts by weight;

[0015] The composition II forming the second material contains: isocyanate B, isocyanate C, polyol B, polyvinyl alcohol, and water II; the polyol B is a dihydric or higher alcohol; the average weight average molecular weight of the polyol B is 60-180 g / mol;

[0016] Relative to 100 parts by weight of isocyanate B, the content of isocyanate C is 80-120 parts by weight, the content of polyol B is 2-8 parts by weight, the content of polyvinyl alcohol is 10-16 parts by weight, and the content of water II is 200-240 parts by weight.

[0017] The second aspect of the present invention provides a polyurethane rubber powder, which is a product prepared by applying the raw material combination described in the first aspect.

[0018] The third aspect of the present invention provides use of the raw material combination described in the first aspect and the polyurethane rubber powder described in the second aspect in building materials.

[0019] The polyurethane glue powder prepared by the raw material combination for polyurethane glue powder provided by the present invention is easy to disperse, stable in storage, and reactive; it can be used in dry-mixed mortar. When the dry-mixed mortar is added with water for construction, the polyurethane glue powder is redispersed and reacted in water to form a polyurethane modified mortar, which can significantly improve the compressive and flexural strengths, especially the flexural performance, of cement mortar products. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] As mentioned above, the first aspect of the present invention provides a raw material combination for polyurethane rubber powder, the combination contains a first material and a second material, and the mass ratio of the first material to the second material is 1:3-5;

[0022] The composition I forming the first material contains: polyol A, isocyanate A, catalyst, protective colloid, emulsifier, water I; the isocyanate A is selected from cycloalkyl diisocyanate and / or xylene diisocyanate; the polyol A is a dihydric or higher alcohol;

[0023] Relative to 100 parts by weight of polyol A, the content of isocyanate A is 8-16 parts by weight, the content of the catalyst is 0.2-0.4 parts by weight, the content of the protective colloid is 8-18 parts by weight, the content of the emulsifier is 0.05-0.4 parts by weight, and the content of water I is 75-95 parts by weight;

[0024] The composition II forming the second material contains: isocyanate B, isocyanate C, polyol B, polyvinyl alcohol, and water II; the polyol B is a dihydric or higher alcohol; the average weight average molecular weight of the polyol B is 60-180 g / mol;

[0025] Relative to 100 parts by weight of isocyanate B, the content of isocyanate C is 80-120 parts by weight, the content of polyol B is 2-8 parts by weight, the content of polyvinyl alcohol is 10-16 parts by weight, and the content of water II is 200-240 parts by weight.

[0026] Preferably, the isocyanate B is selected from at least one of toluene diisocyanate and isophorone diisocyanate; preferably, the isocyanate B is toluene diisocyanate.

[0027] Preferably, the isocyanate C comprises diphenylmethane diisocyanate having an average NCO functionality of at least 2.0.

[0028] More preferably, the isocyanate C is diphenylmethane diisocyanate having an average NCO functionality of 2.3-2.7. The inventors found that under this preferred embodiment, the obtained polyurethane powder has better anti-caking properties and has better compression and flexural properties when used in mortar.

[0029] Preferably, the weight average molecular weight of the polyol A is 800-30000 g / mol.

[0030] More preferably, the weight average molecular weight of the polyol A is 1000-8000 g / mol.

[0031] Particularly preferably, the polyol A is a polyether polyol and / or a polyester polyol.

[0032] Preferably, the polyol B is 1,4-butanediol.

[0033] Preferably, the catalyst is selected from at least one of a polyurethane amine catalyst and a metal organic catalyst.

[0034] More preferably, the catalyst is selected from at least one of triethylamine, dimethylcyclohexylamine and dibutyltin dilaurate.

[0035] Preferably, the emulsifier is selected from at least one of 1306L of Ningyuan Chemical and CQ100s of Evonik.

[0036] Preferably, the protective colloid is prepared by a method comprising the following steps:

[0037] In the presence of an initiator, acrylamide, acrylic acid and hydroxyethyl methacrylate are reacted to obtain the protective colloid;

[0038] The mass ratio of acrylamide, acrylic acid and hydroxyethyl methacrylate is 1:1:0.8-1.5:0.3-0.6. The inventors found that under this preferred embodiment, the obtained polyurethane powder has better anti-caking property and has better compression and flexural properties when applied in mortar.

[0039] Preferably, the protective colloid is prepared by a method comprising the following steps, the method further comprising:

[0040] In the presence of water and an initiator, a mixture containing acrylamide, acrylic acid and hydroxyethyl methacrylate is added dropwise to react to obtain the protective colloid;

[0041] The mass ratio of acrylamide, acrylic acid and hydroxyethyl methacrylate is 1:0.8-1.5:0.3-0.6.

[0042] Preferably, the initiator is ammonium persulfate.

[0043] More preferably, the reaction is carried out under stirring conditions, and the reaction conditions include: temperature of 65-75° C., time of 4.5-5.5 h, and stirring speed of 300-800 rpm.

[0044] Particularly preferably, the mixture containing acrylamide, acrylic acid and hydroxyethyl methacrylate is added dropwise at a rate of 10-20 wt% / min of the total weight.

[0045] Preferably, relative to 100 parts by weight of the mixture, the amount of the initiator is 0.4-0.6 parts by weight, and the amount of water is 80-120 parts by weight.

[0046] Preferably, the pH value of the protective colloid is 3.5-4.5.

[0047] Preferably, the first material is prepared by a method comprising the following steps, wherein the method is carried out using the aforementioned composition I:

[0048] SI-1, in the presence of a protective gas, subjecting polyol A, isocyanate A and a catalyst to a first mixing reaction to obtain a first product;

[0049] SI-2, in the presence of water I, subjecting the emulsifier to a second mixing reaction with the first product to obtain a second product;

[0050] SI-3, performing a third mixing reaction on the protective colloid and the second product to obtain a third product;

[0051] SI-4, mixing the third product with ammonia water and sulfuric acid in sequence, and drying the obtained product to obtain the first material;

[0052] Wherein, the emulsifier is added in a slow dripping manner, and the speed of the slow dripping is 0.01-0.1 g / min;

[0053] The protective colloid is added in batches, and the conditions for the batch addition are: the amount of each addition is 30-35wt% of the total amount, and the interval time is 15-20min. The inventors found that under this preferred specific implementation, the obtained polyurethane powder has better anti-caking properties and has better compression and flexural properties when used in mortar.

[0054] Preferably, the protective gas is selected from at least one of nitrogen and helium.

[0055] Preferably, the concentration of the aqueous ammonia is 4-6 wt %.

[0056] Preferably, the concentration of the sulfuric acid is 4-6 wt %.

[0057] More preferably, the first mixing reaction, the second mixing reaction, and the third mixing reaction are all carried out under stirring conditions;

[0058] The conditions of the first mixing reaction include: stirring speed of 400-1000 rpm, temperature of 65-75° C., and time of 2.5-3.5 h;

[0059] The conditions of the second mixing reaction include: stirring speed of 800-1200 rpm, temperature of 65-75° C., and time of 0.5-0.75 h;

[0060] The conditions of the third mixing reaction include: stirring speed of 1000-1200 rpm, temperature of 75-85° C., and time of 3.0-3.5 h.

[0061] Preferably, in step SI-4, the mixing step comprises: mixing the third product with ammonia water I, letting the obtained mixture I stand for 20-40 minutes, and then mixing with sulfuric acid II, and drying the obtained mixture II to obtain the first material; the amount of ammonia water is such that the pH value of the initial system of the mixture I is 8.8-9.0; the amount of sulfuric acid is such that the pH value of the initial system of the mixture II is 2.8-3.0.

[0062] Preferably, the first material is a first material having an average particle diameter of no more than 0.1 mm after grinding.

[0063] Preferably, the second material is prepared by a method comprising the following steps, wherein the method is carried out using the aforementioned composition II:

[0064] SII-1, bringing water II into first contact with a dispersant to obtain an intermediate material I;

[0065] SII-2, contacting isocyanate B, isocyanate C and the intermediate material I for the second time to obtain an intermediate material II;

[0066] SII-3, contacting the polyol B with the intermediate material II for the third time to obtain an intermediate material III;

[0067] SII-4, contacting polyvinyl alcohol with the intermediate material III for the fourth time to obtain the second material;

[0068] Wherein, the first contact is carried out under stirring conditions, and the conditions for the first contact include: a stirring speed of 950-1050 rpm, a temperature of 65-70° C., and a time of 0.2-0.3 h.

[0069] Preferably, the dispersant is selected from at least one of DISPERBYK-168, DISPERBYK-142 and DISPERBYK-169 produced by BYK Chemical.

[0070] More preferably, the conditions for the second contact include: a stirring speed of 950-1050 rpm, a temperature of 35-40° C., and a time of 9-11 min.

[0071] Further preferably, the polyol B is added in a slow dripping manner at a speed of 0.2-1 g / min. The inventors found that under this preferred embodiment, the obtained polyurethane powder has better anti-caking properties and has better compression and flexural properties when used in mortar.

[0072] Particularly preferably, the polyvinyl alcohol is added in portions, and the conditions for the portion-wise addition are: the amount of each addition is 45-55 wt % of the total amount, and the interval time is 5-10 min.

[0073] Preferably, the conditions for the third contact include: a stirring speed of 950-1050 rpm, a temperature of 35-40° C., and a time of 40-60 min.

[0074] Preferably, the conditions for the fourth contact include: a stirring speed of 950-1050 rpm, a temperature of 35-40° C., and a time of 1-1.5 h.

[0075] Preferably, the method further comprises: washing the product obtained by the fourth contact with water three times, and then drying the product to obtain the second material.

[0076] As mentioned above, the second aspect of the present invention provides a polyurethane rubber powder, which is a product made by applying the raw material combination described in the first aspect.

[0077] Preferably, the method for preparing the polyurethane rubber powder comprises: mixing a mixture material containing a combination of raw materials for polyurethane rubber powder to obtain the polyurethane rubber powder.

[0078] It should be noted that the present invention has no special requirements on the conditions for mixing the mixture containing the raw material combination for polyurethane rubber powder, as long as it can be mixed evenly; illustratively, the mixing conditions can be: temperature of 25-40°C, stirring speed of 60-180rpm, and time of 5-12min.

[0079] As mentioned above, the third aspect of the present invention provides the use of the raw material combination for polyurethane rubber powder described in the first aspect and the polyurethane rubber powder described in the second aspect in building materials.

[0080] The present invention will be described in detail below through examples.

[0081] In the following examples, unless otherwise specified, the experimental instruments, reagents and raw materials involved are all commercially available, and the reagents are all analytically pure products.

[0082] In the following examples, each part by weight represents 100 g unless otherwise specified.

[0083] raw material

[0084] Polyol A: castor oil modified polyol, brand D1000, purchased from Vantelus; castor oil branched polyol, brand SETATHANE D1150, purchased from Allnex;

[0085] Isocyanate A: cycloalkyl diisocyanate (hydrogenated xylylene diisocyanate), brand name Takenate 600, purchased from Mitsui Co., Japan; xylylene diisocyanate, brand name Takenate 500, purchased from Mitsui Co., Japan;

[0086] Catalyst: triethylamine;

[0087] Emulsifier: CQ100S, purchased from Evonik;

[0088] Isocyanate B: toluene diisocyanate;

[0089] Isocyanate C: polymeric MDI, brand PM-200, purchased from Wanhua Chemical Company;

[0090] Polyol B: 1,4-butanediol;

[0091] Dispersant: DISPERBYK-169, purchased from BYK Chemicals;

[0092] Protective colloid: prepared by the following preparation method:

[0093] In the presence of 100 g of water and 0.5 g of ammonium persulfate, a mixture containing 40 g of acrylamide, 40 g of acrylic acid and 20 g of hydroxyethyl methacrylate is added dropwise to react to obtain the protective colloid; the reaction conditions include: temperature of 70° C., time of 5 h, stirring speed of 500 rpm; the dropping speed is 15 wt% / min of the total weight.

[0094] Preparation Example A-1

[0095] This preparation example is used to illustrate that the first material of the present invention is prepared according to the formula and process parameters in Table 1 and the following method:

[0096] SI-1. In the presence of nitrogen, polyol A, isocyanate A and a catalyst are subjected to a first mixing reaction to obtain a first product; the conditions of the first mixing reaction are: a stirring speed of 800 rpm, a temperature of 70° C., and a time of 3 h;

[0097] SI-2, in the presence of water I, the emulsifier and the first product are subjected to a second mixing reaction to obtain a second product; the conditions of the second mixing reaction are: a stirring speed of 1000 rpm, a temperature of 70° C., and a time of 0.6 h;

[0098] SI-3, subjecting the protective colloid and the second product to a third mixing reaction to obtain a third product; the conditions of the third mixing reaction are: a stirring speed of 1000 rpm, a temperature of 80° C., and a time of 3.0 h.

[0099] SI-4. The third product is mixed with 5wt% ammonia water in sequence I, the obtained mixture I is allowed to stand for 30 minutes, and then mixed with sulfuric acid II, the obtained mixture II is dried, and then ground to obtain the first material with an average particle diameter of 0.1mm; the amount of ammonia water is such that the pH value of the initial system of the mixture I is 9.0; the amount of 5wt% sulfuric acid is such that the pH value of the initial system of the mixture II is 3.0.

[0100] The emulsifier is added in a slow dripping manner; the protective colloid is added in portions.

[0101] Unless otherwise specified, the remaining preparation examples were carried out using a process similar to that of Preparation Example A-1, except that the formulas and process parameters used in each preparation example were different, as shown in Table 1 (Note: the parameters not listed in Table 1 are the same as the corresponding parameters in Preparation Example A-1).

[0102] Table 1

[0103]

[0104] Preparation Example A-3

[0105] This preparation example adopts a similar process to that of Preparation Example A-1, except that hydroxyethyl cellulose (brand B30K, manufactured by Lotte, Korea) of equal quality is used to replace the protective colloid in Preparation Example A-1.

[0106] The rest is the same as Preparation Example A-1.

[0107] The first material A-3 was prepared.

[0108] Preparation Example A-4

[0109] This preparation example adopts a similar process to that of Preparation Example A-1, except that the dropping speed of the emulsifier in this preparation example is 0.12 g / min.

[0110] The rest is the same as Preparation Example A-1.

[0111] The first material A-4 was prepared.

[0112] Preparation Example A-5

[0113] This preparation example adopts a similar process to that of Preparation Example A-1, except that the protective colloid is added in batches in this preparation example: the amount each time is 33.3 wt% of the total amount, and the interval time is 25 min.

[0114] The rest is the same as Preparation Example A-1.

[0115] The first material A-5 was prepared.

[0116] Preparation Example DA-1

[0117] This preparation example adopts a similar process to that of Preparation Example A-1, except that this preparation example uses 1,4-butanediol of equal mass to replace the polyol A in Preparation Example A-1.

[0118] The rest is the same as Preparation Example A-1.

[0119] The first material DA-1 was prepared.

[0120] Preparation Example DA-2

[0121] This preparation example adopts a similar process to that of Preparation Example A-1, except that toluene diisocyanate of equal mass is used to replace isocyanate A in Preparation Example A-1.

[0122] The rest is the same as Preparation Example A-1.

[0123] The first material DA-2 was prepared.

[0124] Preparation Example B-1

[0125] This preparation example is used to illustrate that the second material of the present invention is prepared according to the formula and process parameters in Table 2 and the following method:

[0126] SII-1, bringing water II into first contact with a dispersant to obtain an intermediate material I;

[0127] SII-2, contacting isocyanate B, isocyanate C and the intermediate material I for the second time to obtain an intermediate material II;

[0128] SII-3. The polyol B is contacted with the intermediate material II for the third time to obtain the intermediate material III. The conditions of the third contact are: stirring speed of 1000 rpm, temperature of 35° C., and time of 50 min.

[0129] SII-4. Polyvinyl alcohol is brought into contact with the intermediate material III for the fourth time, and the obtained product is washed three times with water and then dried to obtain the second material; the conditions of the fourth contact are: stirring speed of 1000 rpm, temperature of 35°C, and time of 1 hour.

[0130] Unless otherwise specified, the remaining preparation examples were carried out using a process similar to that of Preparation Example B-1, except that the formulas and process parameters used in each preparation example were different, see Table 2 for details (Note: the parameters not listed in Table 2 are the same as the corresponding parameters in Preparation Example B-1).

[0131] Table 2

[0132]

[0133]

[0134] Preparation Example B-3

[0135] This preparation example is carried out using a method similar to that of Preparation Example B-1, except that this preparation example uses diphenylmethane diisocyanate (brand name MDI-50, manufacturer: Wanhua Chemical) with an average NCO functionality of 2.0 to replace isocyanate C in Preparation Example B-1.

[0136] The rest is the same as Preparation Example B-1.

[0137] The second material B-3 was prepared.

[0138] Preparation Example B-4

[0139] This preparation example was carried out using a method similar to that of Preparation Example B-1, except that the conditions for the second contact in this preparation example were: a stirring speed of 1050 rpm, a temperature of 40° C., and a time of 12 min.

[0140] The rest is the same as Preparation Example B-1.

[0141] The second material B-4 was prepared.

[0142] Preparation Example B-5

[0143] This preparation example was carried out using a method similar to that of Preparation Example B-1, except that the dropping speed of polyol B in this preparation example was 1.1 g / min.

[0144] The rest is the same as Preparation Example B-1.

[0145] The second material B-5 was prepared.

[0146] Preparation Example B-6

[0147] This preparation example was carried out using a method similar to that of Preparation Example B-1, except that in this preparation example, polyvinyl alcohol was added in portions at a rate of 50 wt % each time and at an interval of 11 min.

[0148] The rest is the same as Preparation Example B-1.

[0149] The second material B-6 was prepared.

[0150] Preparation Example DB-1

[0151] This preparation example is carried out in a similar manner to that of Preparation Example B-1, except that an equal amount of xylylene diisocyanate is used to replace isocyanate B in Preparation Example B-1.

[0152] The rest is the same as Preparation Example B-1.

[0153] The second material DB-1 was prepared.

[0154] Preparation Example DB-2

[0155] This preparation example is carried out in a similar manner to that of Preparation Example B-1, except that toluene diisocyanate of equal mass is used to replace isocyanate C in Preparation Example B-1.

[0156] The rest is the same as Preparation Example B-1.

[0157] The second material DB-2 was prepared.

[0158] Preparation Example DB-3

[0159] This preparation example is carried out by a method similar to that of Preparation Example B-1, except that an equal amount of polyol A in Preparation Example A-1 is used to replace polyol B in Preparation Example B-1.

[0160] The rest is the same as Preparation Example B-1.

[0161] The second material DB-3 was prepared.

[0162] Example 1

[0163] This example is used to illustrate that the polyurethane rubber powder of the present invention is prepared according to the formula in Table 3 and the following method:

[0164] The first material and the second material are mixed to obtain the polyurethane rubber powder; the mixing conditions may be: temperature of 30° C., stirring speed of 80 rpm, and time of 6 min.

[0165] Unless otherwise specified, the remaining examples were carried out using a process similar to that of Example 1, except that the formulas used in each example are specifically shown in Table 3 (Note: the parameters not listed in Table 3 are the same as the corresponding parameters in Example 1).

[0166] Table 3

[0167] Example 1 Example 2 Example 3 Example 4 First Material A-1 A-2 A-1 A-1 Second material B-1 B-2 B-3 B-4 The mass ratio of the first material to the second material 1:3 1:5 1:3 1:3 name S1 S2 S3 S4

[0168] Table 3 (Continued)

[0169] Example 5 Example 6 Example 7 Example 8 First Material A-1 A-1 A-3 A-4 Second material B-5 B-6 B-1 B-1 The mass ratio of the first material to the second material 1:3 1:3 1:3 1:3 name S5 S6 S7 S8

[0170] Table 3 (Continued)

[0171] Example 9 Example 10 Comparative Example 1 Comparative Example 2 First Material A-5 A-6 DA-1 DA-2 Second material B-1 B-6 B-1 B-1 The mass ratio of the first material to the second material 1:3 1:3 1:3 1:3 name S9 S10 DS1 DS2

[0172] Table 3 (Continued)

[0173] Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 First Material A-1 A-1 A-1 A-1 Second material DB-1 DB-2 DB-3 B-1 The mass ratio of the first material to the second material 1:3 1:3 1:3 1:8 name DS3 DS4 DS5 DS6

[0174] Test Case

[0175] The prepared polyurethane rubber powder was subjected to the following performance tests, and the specific test methods are as follows:

[0176] (1) Anti-caking property: 10 wt% of anti-caking agent (calcium hydroxide with an average particle size of 15 μm and white carbon black with an average particle size of 5 μm (w:w=9:1)) was added to the rubber powder, mixed evenly, and then loaded into a stainless steel tube with bolt fasteners, and then a pressure of 5 kg was applied using a metal plunger. The pressure was maintained and placed in a 50°C oven for 16 hours. After cooling to room temperature, the rubber powder was taken out of the stainless steel tube, crushed into powder, and then sieved with a sieve with an aperture of 0.15 mm to quantitatively determine the anti-caking property.

[0177] The more lumps of latex powder that cannot pass through the sieve, the worse the anti-caking performance.

[0178] (a) The residue is less than 10 wt% and is considered to have very good anti-caking properties;

[0179] (b) 10-20wt% indicates good anti-caking performance;

[0180] (c) 20-40wt% indicates average anti-caking performance;

[0181] (d) greater than 40 wt% indicates poor anti-caking performance and the latex powder no longer has fluidity after being crushed.

[0182] (2) Average particle size of the emulsion re-dissolved particles (the emulsion re-dissolved particles are obtained by dispersing the polyurethane rubber powder (10 g) obtained in the above example in water (100 g)): The particle size and particle size distribution of the emulsion re-dissolved particles are tested using a laser particle size analyzer, and the average particle size and particle size distribution of the emulsion particles are calculated using the obtained distribution diagram.

[0183] (3) Flexural strength, compression strength, compression-flexural ratio, setting time, and 14d tensile bond strength of ordinary cement plaster mortar: The test was carried out in accordance with GBT 17671-1999 "Test Method for Strength of Cement Mortar" and GBT 25181-2010 "Premixed Mortar" for dry-mixed ordinary plaster mortar. The composition of ordinary cement plaster mortar is as follows:

[0184] The present invention provides 0.5 g of polyurethane powder, 150 g of PO42.5 cement, 849.02 g of 0-4.75 mm machine-made sand, 0.15 g of cellulose ether (HPMC10W, Tiansheng Company), 0.3 g of starch ether (CASUCOL 301, Avibe Company), 0.03 g of air entraining agent (K12, Hunan Zhengmude New Material Technology Co., Ltd.), and 135 g of water.

[0185] The test results are shown in Table 4.

[0186] Table 4

[0187]

[0188] As can be seen from Table 4, the reactive polyurethane powder prepared by the method provided by the present invention has good anti-caking property and qualified redispersibility, and its compressive and flexural properties are significantly improved in ordinary cement plaster mortar, the compression-flexural ratio is not more than 3 (excellent anti-cracking performance), the 14d tensile bonding strength is significantly improved, the setting time is qualified, and it can be used in continuous construction machinery and equipment.

[0189] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A raw material combination for polyurethane rubber powder, characterized in that: The combination contains a first material and a second material, and the mass ratio of the first material to the second material is 1:3-5; The composition I forming the first material contains: polyol A, isocyanate A, catalyst, protective colloid, emulsifier, water I; the isocyanate A is selected from cycloalkyl diisocyanate and / or xylene diisocyanate; the polyol A is a dihydric or higher alcohol; Relative to 100 parts by weight of polyol A, the content of isocyanate A is 8-16 parts by weight, the content of the catalyst is 0.2-0.4 parts by weight, the content of the protective colloid is 8-18 parts by weight, the content of the emulsifier is 0.05-0.4 parts by weight, and the content of water I is 75-95 parts by weight; The composition II forming the second material contains: isocyanate B, isocyanate C, polyol B, polyvinyl alcohol, and water II; the polyol B is a dihydric or higher alcohol; the average weight average molecular weight of the polyol B is 60-180 g / mol; Relative to 100 parts by weight of isocyanate B, the content of isocyanate C is 80-120 parts by weight, the content of polyol B is 2-8 parts by weight, the content of polyvinyl alcohol is 10-16 parts by weight, and the content of water II is 200-240 parts by weight.

2. The raw material combination according to claim 1, characterized in that: The isocyanate B is selected from at least one of toluene diisocyanate and isophorone diisocyanate; preferably, the isocyanate B is toluene diisocyanate; And / or, the isocyanate C comprises diphenylmethane diisocyanate having an average NCO functionality of at least 2.0; preferably, the isocyanate C comprises diphenylmethane diisocyanate having an average NCO functionality of 2.3-2.

7.

3. The raw material combination according to claim 1 or 2, characterized in that: The average weight average molecular weight of the polyol A is 800-30000 g / mol; preferably 1000-8000 g / mol; more preferably polyether polyol and / or polyester polyol; And / or, the polyol B is 1,4-butanediol.

4. The raw material combination according to any one of claims 1 to 3, characterized in that: The protective colloid is prepared by a method comprising the following steps: In the presence of an initiator, acrylamide, acrylic acid and hydroxyethyl methacrylate are reacted to obtain the protective colloid; The mass ratio of acrylamide, acrylic acid and hydroxyethyl methacrylate is 1:0.8-1.5:0.3-0.

6.

5. The raw material combination according to any one of claims 1 to 4, characterized in that: The first material is prepared by a method comprising the following steps, wherein the method is carried out using the composition I described in any one of claims 1 to 4: SI-1, in the presence of a protective gas, subjecting polyol A, isocyanate A and a catalyst to a first mixing reaction to obtain a first product; SI-2, in the presence of water I, subjecting the emulsifier to a second mixing reaction with the first product to obtain a second product; SI-3, performing a third mixing reaction on the protective colloid and the second product to obtain a third product; SI-4, mixing the third product with ammonia water and sulfuric acid in sequence, and drying the obtained product to obtain the first material; Wherein, the emulsifier is added in a slow dripping manner, and the speed of the slow dripping is 0.01-0.1 g / min; The protective colloid is added in portions, and the conditions for the portion-wise addition are: the amount of each addition is 30-35wt% of the total amount, and the interval time is 15-20min.

6. The raw material combination according to claim 5, characterized in that: The first mixing reaction, the second mixing reaction, and the third mixing reaction are all carried out under stirring conditions; The conditions of the first mixing reaction include: stirring speed of 400-1000 rpm, temperature of 65-75° C., and time of 2.5-3.5 h; The conditions of the second mixing reaction include: stirring speed of 800-1200 rpm, temperature of 65-75° C., and time of 0.5-0.75 h; The conditions of the third mixing reaction include: stirring speed of 1000-1200 rpm, temperature of 75-85° C., and time of 3.0-3.5 h.

7. The raw material combination according to any one of claims 1 to 6, characterized in that: The second material is prepared by a method comprising the following steps, wherein the method is carried out using the composition II described in any one of claims 1 to 4: SII-1, bringing water II into first contact with a dispersant to obtain an intermediate material I; SII-2, contacting isocyanate B, isocyanate C and the intermediate material I for the second time to obtain an intermediate material II; SII-3, contacting the polyol B with the intermediate material II for the third time to obtain an intermediate material III; SII-4, contacting polyvinyl alcohol with the intermediate material III for the fourth time to obtain the second material; Wherein, the first contact is carried out under stirring conditions, and the conditions for the first contact include: a stirring speed of 950-1050 rpm, a temperature of 65-70° C., and a time of 0.2-0.3 h.

8. The raw material combination according to claim 7, characterized in that: The conditions of the second contact include: stirring speed of 950-1050 rpm, temperature of 35-40° C., and time of 9-11 min; And / or, the polyol B is added in a slow dripping manner, and the slow dripping speed is 0.2-1 g / min; And / or, the polyvinyl alcohol is added in portions, and the conditions for the portion-wise addition are: the amount of each addition is 45-55wt% of the total amount, and the interval time is 5-10min.

9. A polyurethane rubber powder, characterized in that: The polyurethane rubber powder is a product prepared by using the raw material combination described in any one of claims 1 to 8.

10. Use of the raw material combination for polyurethane rubber powder according to any one of claims 1 to 8 and the polyurethane rubber powder according to claim 9 in building materials.